FAITH IN LOCAL GOVERNMENT: THE EMERGENCE OF RELIGION IN THE POLITICS OF AN INNER LONDON BOROUGH 1975-2006 - Smith, Greg (Politikologija religije, 2010)
This paper examines the impact religious affiliation and faith commitment exerts on the political life of one inner-London borough. It gives a historical sketch of the interaction of faith and politics in the period from about 1975-2006 and attempts some explanation of the patterns of voting in local elections and political involvement by members of the many faith communities which are found in the borough. The key to this is seen in the changing urban ecology of the area and the communal interests of particular ethno-religious groups who have striven and, to a measure, succeeded in gaining representation in local politics over this period. Drawing on many years participation observation, an analysis of the religious and community affiliations of elected members, and a series of interviews with Councillors and faith leaders, it reflects political issues and conflicts involving faith communities. Evidence will be presented which suggests that while many Christians involved in politics are primarily motivated individually by beliefs and values which centre on service to the whole community, politicians from other faith communities are more likely to be cast in a role as communal representatives and advocates of particular sections of the community.